Eco‐evolutionary perspectives of the dynamic relationships linking senescence and cancer. (22nd July 2019) - Lemaître, Jean‐François; Pavard, Samuel; Giraudeau, Mathieu; Vincze, Orsolya; Jennings, Geordie; Hamede, Rodrigo; Ujvari, Beata; Thomas, Frédéric
Abstract: Evidence for actuarial senescence (i.e. the decrease in survival with increasing age) is now widespread across the tree of life. However, demographic senescence patterns are highly variable both between and within species. To understand these variations, there is an urgent need to go beyond aggregated mortality rates and to investigate how age‐specific causes of mortality in animals interact with age‐specific physiological performance. We address this question in the context of cancers. Cancer is a leading cause of death in human populations and has recently been shown to be more prevalent across species than previously thought. Since anthropogenic perturbations drastically increase cancer rates in wild populations of animals, deciphering the complex interactions between senescence and cancer now constitutes a key challenge in evolutionary ecology. Based on classical evolutionary theories of ageing, we first demonstrate that the occurrence of cancers might constitute an underestimated piece of the life‐history jigsaw. We propose that the selection for an increased allocation of resources towards growth and reproduction during early life might potentially favour cancer development, a life‐history pathway that might be functionally mediated by the process of immunosenescence. While we discuss the relevance of other proximate mechanisms suggesting that cancer arises as a direct consequence of senescence, we also argue that cancer itself can promote senescence by notably increasing the amount of resources required for somatic maintenance. Contrary to theoretical predictions, recent empirical evidence suggests that senescence is an asynchronous process among physiological functions. At the same time, the timing of occurrence varies widely between the different types of cancers. We suggest that similar evolutionary forces might shape the synchronicity of senescence and cancer patterns, which emphasize the tight and complex relationships linking these processes. We propose a conceptual background to lay down the foundations and the directions of future research projects aiming to disentangle the dynamic relationship between the evolution of cancer and senescence. We argue that studies embracing these research directions will markedly improve our understanding of both cancer prevalence and timing at the individual, population and species level. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.